Synchronous polar winter starphotometry and lidar measurements at a High Arctic station - K. Baibakov; N. T. O'Neill; L. Ivanescu; T. J. Duck; C. Perro; A. Herber; K.-H. Schulz; O. Schrems (Atmospheric Measurement Techniques, 2015)
We present recent progress on nighttime retrievals of aerosol and cloud optical properties over the PEARL (Polar Environmental Atmospheric Research Laboratory) station at Eureka (Nunavut, Canada) in the High Arctic (80° N, 86° W). In the spring of 2011 and 2012, a star photometer was employed to acquire aerosol optical depth (AOD) data, while vertical aerosol and cloud backscatter profiles were measured using the CANDAC Raman Lidar (CRL). We used a simple backscatter coefficient threshold (β thr ) to distinguish aerosols from clouds and, assuming that aerosols were largely fine mode (FM)/sub-micron, to distinguish FM aerosols from coarse mode (CM)/super-micron cloud or crystal particles. Using prescribed lidar ratios, we computed FM and CM AODs that were compared with analogous AODs estimated from spectral star photometry. We found (β thr dependent) coherences between the lidar and star photometer for both FM events and CM cloud and crystal events with averaged, FM absolute differences being <∼0.03 when associated R 2 values were between 0.2 and 0.8. A β thr sensitivity study demonstrated that zero crossing absolute differences and R 2 peaks were in comparable regions of the β thr range (or physical reasons were given for their disparity). The utility of spectral vs. temporal cloud screening of star photometer AODs was also illustrated. In general our results are critical to building confidence in the physical fidelity of derived, weak amplitude, star photometry AODs and, in turn, towards the development of AOD climatologies and validation databases for polar winter models and satellite sensors.